Exosomes: Emerging Therapeutic Nanocarriers in Drug Delivery & Disease Diagnostics - Shreyash A. Diwakar; Chirag G. Chavda; Shreyash A. Diwakar2; Bhavin D. Pandya; Kautuk P. Shah (Asian Journal of Pharmaceutical Research and Development, 2026)
Exosomes are naturally occurring extracellular vesicles with diameters ranging from approximately 30 to 150 nm, secreted by a wide variety of cell types. They serve as important mediators of intercellular communication by transporting bioactive molecules such as proteins, lipids, DNA, RNA, and other nucleic acids between cells. Owing to their inherent biocompatibility, structural stability, low immunogenicity, and ability to traverse biological barriers, including the blood–brain barrier, exosomes have emerged as highly promising nanocarriers for therapeutic and diagnostic applications. Unlike many synthetic delivery systems, such as liposomes and polymeric nanoparticles, exosomes exhibit enhanced resistance to metabolic degradation and possess natural targeting capabilities. Generated during various physiological and pathological processes, these vesicles have gained considerable interest in the field of precision medicine for their potential to address disease mechanisms at the molecular level. This review outlines the fundamental biology of exosomes, including their origin, classification, physicochemical characteristics, and cargo composition relevant to drug delivery. It further explores their therapeutic potential in areas such as cancer treatment, neurological diseases, and tissue regeneration. In addition, the application of exosome-based systems for the delivery of small-molecule drugs, proteins, and nucleic acids is discussed, along with an overview of leading organizations and research groups actively involved in the development and clinical evaluation of exosome-derived therapeutic platforms.